Assessment of a Master of Education Counselling Application Selection Process Using Rasch Analysis and Generalizability Theory - Sebok, Stefanie S.; MacMillan, Peter D. (Canadian Journal of Counselling and Psychotherapy, 2014)
This study was designed to evaluate an application selection process for a Master of Education counselling program in Canada using the Many-Facet Rasch Model (MFRM) and Generalizability Theory (G-Theory). Current literature pertaining specifically to counselling admissions is essentially absent. This study investigated the items used to score and rank applicants as well as rater characteristics for each of the members of the application selection committee. The design, results, and findings have implications for admissions procedures and practices at other universities within Canada. Overall, the MFRM and G-Theory functioned as appropriate measurement tools for assessing counselling admission items, raters, and applicants.